2018
DOI: 10.1007/s40259-018-0303-4
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Immune Checkpoint Inhibitors Targeting PD-1/PD-L1 and Other Emerging Checkpoint Pathways

Abstract: Advances in harnessing the immune system for cancer treatment have been spectacular in recent years as witnessed by the approval of a number of antibodies targeting the PD-1/PD-L1 immune checkpoint pathway spanning an expanding list of indications. However, it is well recognized that while these antibodies show impressive clinical activity, they suffer from shortcomings including the failure to show response in a majority of patients, their need to be administered by intravenous injection, and immune-related a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 58 publications
0
64
0
Order By: Relevance
“…In addition, the PD-1 receptor ligand (PD-L1) antibodies (BMS-936559 and atezolizumab) have been studied for treating melanoma in preclinical mouse models and clinical trials [2,8]. However, the monoclonal antibodies has some disadvantages such as the immunogenicity, lower bioavailability, poor solid tumor tissue distribution and difficult controlled pharmacokinetics, and thus antibody related toxicities [9][10][11][12][13]. In contrast, the small molecules posses good affinity, specificity and oral bioavailability without the immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the PD-1 receptor ligand (PD-L1) antibodies (BMS-936559 and atezolizumab) have been studied for treating melanoma in preclinical mouse models and clinical trials [2,8]. However, the monoclonal antibodies has some disadvantages such as the immunogenicity, lower bioavailability, poor solid tumor tissue distribution and difficult controlled pharmacokinetics, and thus antibody related toxicities [9][10][11][12][13]. In contrast, the small molecules posses good affinity, specificity and oral bioavailability without the immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical inhibitors for targeting the PD-1/PD-L1 pathway or PD-1/PD-L1 interaction, such as small molecules, macrocyclic peptides, peptides and peptidomimetics, have been reported [9,14]. Several small molecule inhibitors of PD-L1 from Bristol-Myers Squibb (BMS) have been studied with the good blockade activity of PD-1/PD-L1 binding [10,13,15]. One of these agents, BMS-202 (N-(2-{[2-Methoxy-6-(2-methyl-biphenyl-3-ylmethoxy)-pyridin-3-ylmethyl]-amino}-ethyl)acetamide), was resynthesized and renamed as PCC0208025 in our lab.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zak et al revealed the molecular features of the human PD-1/PD-L1 interaction based on the X-ray structure of the complex, and several hot spots located on the PD-L1 molecule were shown to be involved in the formation of the complex (15,30). To date, several small molecules, macrocyclic peptides and peptide mimetics targeting the PD-1/PD-L1 interaction have been reported (8,18,19), primarily in patent applications, but almost no fully validated and qualified therapeutics exist. Recently, the binding action and biological activities of potent small molecule inhibitors of PD-1/PD-L1 have been reported by Bristol-Myers Squibb (BMS) (1,31,32).…”
Section: Development Of Humanized Nog-dko Mice Six-mentioning
confidence: 99%
“…No agonist of inhibitory checkpoint molecules or antagonists of stimulatory checkpoint molecules have been tested in clinical trials as yet, and this is also the case for CeD. However, development of small-molecules targeting checkpoint molecules such as OX40, ICOS, PD-1 and TIGIT is an area of intense research [42]. A worry is that these therapies may increase the risk of contracting malignant diseases (Box 5).…”
Section: Targeting Immune Checkpointsmentioning
confidence: 99%